2021
DOI: 10.25259/sni_536_2021
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of internal carotid artery dissection associated with elongated styloid process: A case report

Abstract: Background: An elongated styloid process is known to cause ischemic stroke. Previous reports claim that internal carotid artery (ICA) dissection due to the elongated styloid process has good outcomes when treated conservatively; however, long-term follow-up has not been attempted and recurrence in the later period has not been reported so far. We report a case of recurrence of symptoms over a decade after the initial onset. Case Description: A 59-year-old man experienced a transient ischemic attack (TIA) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The point that when the involvement occurs in the internal carotid artery the patient can report a headache that extends from the ophthalmic region to the occipital, and can often be confused with a headache, which ends up inducing underdiagnosis (CAVALCANTE et al, 2017). Still, other studies report that Carotid Artery Syndrome may be associated with the occurrence of transient cerebral ischemic events (MILLÁN et al, 2019;RAFARE;CHAGAS, 2019;SHAYGANFAR et al, 2018;YOKOYA et al, 2021).…”
Section: Stretching Of the Styloid Process And Eagle Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The point that when the involvement occurs in the internal carotid artery the patient can report a headache that extends from the ophthalmic region to the occipital, and can often be confused with a headache, which ends up inducing underdiagnosis (CAVALCANTE et al, 2017). Still, other studies report that Carotid Artery Syndrome may be associated with the occurrence of transient cerebral ischemic events (MILLÁN et al, 2019;RAFARE;CHAGAS, 2019;SHAYGANFAR et al, 2018;YOKOYA et al, 2021).…”
Section: Stretching Of the Styloid Process And Eagle Syndromementioning
confidence: 99%
“…There are also reports in the literature of the occurrence of reversible transient ischemic attacks, with the presence of ophthalmic symptoms and episodes of presyncope due to compression of the carotid artery, as well as decreased blood flow in the middle cerebral artery caused by the elongation of the styloid process (JALISI; JAMAL; GRILLONE; 2017; MAHMOUD; ASHOUR; 2020; SAMPAIO et al, 2021;YOKOYA et al, 2021). Borges et al (2021) state that even in the absence of symptomatology reported by the patient, it is also important to diagnose cases in which stretching of the styloid process is observed, since in the future these individuals have greater chances of presenting them.…”
Section: Introductionmentioning
confidence: 99%